Micromechanical modeling of effective behavior of anisotropic porous ductile materials - Ferreira, Ayrton Ribeiro (2019)
The manufacturing of ductile materials generally inserts impurities into their microscopic composition. These impurities may detach from the surrounding matrix and even crack along progressive deformation. Due to the consequent incapacity of these undesirable particles of supporting any stress, these ductile materials are equivalently assumed to be porous. Porosity has been effectively shown to play a fundamental role in the mechanisms of ductile fracture. Many micromechanical models have been proposed since the 1970s with the aim of mathematically describing these mechanisms. Among them, the acclaimed Gurson model combines the averaging homogenization technique with the kinematic theorem of Limit Analysis to estimate the macroscopic yield criterion and porosity evolution law of porous ductile materials. However, the Gurson model and most of its extensions only account for isotropic ductile fracture. Thus, the purpose of the present work is to contribute to the conception of yield criteria for anisotropic porous ductile rupture. Three main contributions are hereby proposed by profiting from similar hypothesis to those of the Gurson model. The first contribution is the assessment of the influence of void morphology on overall yield criteria for those classes of materials. The second is the inclusion of an anisotropic yield criterion in the material matrix so that the macroscopic behavior presents matrix-induced anisotropy even for spherical cavities. The third and last advancement consists of generalizing the material matrix yield criterion of the Gurson model in order to include a linear transformation-based class of yield functions that has been widely used to represent specific high strength aluminum alloys. The results hereby presented highlight the consistency and robustness of the three formulations. Moreover, the role of the porosity on the modeling of yield behavior of aluminum alloys encourages further work regarding experimental parameter characterization.